Islam Beyond Orientalism: To what extent does the category 'religion' describe what Islam is? - Allam, Hossam Ed-Deen (Universitas Islam Internasional Indonesia, 2022)
In recent decades, the validity and the sufficiency of the term ‘religion' as an analytical category have been examined by many religious studies scholars. This essay urges Muslim scholars, sociologists, and scholars of religion to be cautious and to direct critical attention to the practice of categorizing the term ‘religion' in their scholarly discourse and in society at large. Such critical deliberations on the use of ‘religion' as an analytical category must occupy a focal position within any meaningful academic discourse pertaining to religious phenomenon in general and Islam in particular. To be more specific, the critical analysis of the term ‘religion,' and of its delineations with seemingly secular categories, must be further constructively incorporated into any academic discourse on religious phenomena or Islamic tradition. Each distinct conception of the term ‘religion,’ as well as its differentiation from other analytical categories, are outcomes of a particular historical occurrence, within the bounds of specific social institutions and interactions, framed by particular traditions and norms. This essay's critical analysis encompasses not only the category of ‘religion' in various geographical and historical settings, but also the conception of ‘religion' in anthropological and sociological literature.